Hypoxia as a biomarker for radioresistant cancer stem cells. (August 2014) - Peitzsch, Claudia; Perrin, Rosalind; Hill, Richard P.; Dubrovska, Anna; Kurth, Ina
Abstract Background: Tumor initiation, growth and relapse after therapy are thought to be driven by a population of cells with stem cell characteristics, named cancer stem cells (CSC). The regulation of their radiation resistance and their maintenance is poorly understood. CSC are believed to reside preferentially in special microenvironmental niches located within tumor tissues. The features of these niches are of crucial importance for CSC self-renewal, metastatic potential and therapy resistance. One of the characteristics of solid tumors is occurrence of less oxygenated (hypoxic regions), which are believed to serve as so-called hypoxic niches for CSC. Purpose: The purpose of this review was the critical discussion of the supportive role of hypoxia and hypoxia-related pathways during cancer progression and radiotherapy resistance and the relevance for therapeutic implications in the clinic. Conclusion: It is generally known since decades that hypoxia inside solid tumors impedes chemo- and radiotherapy. However, there is limited evidence to date that targeting hypoxic regions during conventional therapy is effective. Nonetheless improved hypoxia-imaging technologies and image guided individualized hypoxia targeted therapy in conjunction with the development of novel molecular targets may be able to challenge the protective effect on the tumor provided by hypoxia.